From fundamental freedom to political and economic ‘hot potato’ in 50 years: Labour mobility and migration within the EU - Dobson, John R.; Sennikova, Irina (Journal of Business Economics and Management, 2007)
The free movement of labour and the creation of a European Labour Market have been the objectives of the European Union since its creation, but it is only with the 2004 enlargement that this has started to become a reality, with substantial numbers of East European workers seeking employment in the old member states. This paper uses the data from the UK Worker Registration Scheme and that compiled by the European Commission to examine the nature of this movement and its impact on the economies of both the existing and the new member states. First Published Online: 14 Oct 2010